Disaster (over-)insurance: The long-term financial and socioeconomic consequences of Hurricane Katrina - Zachary Bleemer; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2017)
Federal disaster insurance - in the form of national flood insurance, the Federal Emergency Management Agency (FEMA), and other programs - is designed to nationally distribute large geography-specific shocks such as earthquakes and hurricanes. This study examines how residents were affected on net by the local long-run impacts of Hurricane Katrina and the subsequent policy response. Using a unique fifteen-year panel of 5 percent of adult Americans' credit reports, we find, ten years after the hurricane, higher rates of insolvency and lower homeownership among inundated residents of New Orleans relative to their nonflooded neighbors. Residents of mostly white and mostly black neighborhoods obtain similar short- and long-term outcomes, though residents of white neighborhoods are more likely to have migrated out of the city. Inundated New Orleans residents appear more likely to have migrated to neighboring states but substantially less likely than nonflooded residents to have migrated north. However, we find that residents of the large Gulf Opportunity Zone (GO Zone) surrounding New Orleans, who were also eligible for various federal programs, obtained net financial benefits in the years after Katrina; a decade later, those residents have higher rates of consumption and homeownership and lower rates of bankruptcy and foreclosure than residents outside the GO Zone. These net gains are found to be progressive - favoring young and low-income residents - and are broadly similar across black and white neighborhoods.
Keywords: D14; H84; Q54; R11; R23; 330; disaster insurance; household finances; homeownership; migration